Effect of nitric oxide modulators on cerebrospinal fluid outflow through the cribriform plate of C57Bl/6 mice - D. V. Petrovsky; V. A. Kim; M. B. Sharapova; D. S. Zuev; A. Zh. Ibrayeva; E. K. Silvanovich; M. P. Moshkin; A. V. Romashchenko (Сибирский научный медицинский журнал, 2024)
Introduction. Beside the excretion of metabolic wastes, the lymphatic system in CNS play a crucial role in the regulation of intracranial pressure that is vital for the organism. One of the possible pathways of cerebrospinal fluid (CSF) drainage is its flow through the foramen of the cribriform plate (CP) into the nasal cavity. Despite the significant contribution of the nasal tract to the overall dynamics of the liquor, not much is known about the mechanisms of this process and how it is regulated. Due to its influence on the tone of blood vessels and peristalsis of lymphatic vessels, nitric oxide (NO) is a powerful modulator of liquor outflow, but its effects on nasal CSF outflow have not been studied yet. Aim and Methods. Using diffusion-weighted magnetic resonance imaging (DW MRI), we characterized the changes in CSF outflow through the CP of C57Bl/6 mice influenced by intranasal application of NO synthesis modulators. Results. In our study, using DW MRI and computer tomography (CT) mapping of the CP, we detected significant CSF outflow through its large dorsal and ventral foramen located along the nasal septum. At the same time, the CSF flow rate through the dorsal orifices of the CP was the highest. In addition, we showed that intranasal introduction of NO donor after 30 min leads to a significant decrease of water diffusion through the CP whereas application of a nonspecific NO synthase inhibitor into the nasal cavity enhances nasal outflow. The effects of the NO modulators did not have any significant spatial patterns; CSF outflow was significantly altered across all CP orifices regardless of their size or localization. Conclusion. The obtained results demonstrate the potential possibility of noninvasive local regulation of liquor dynamics, which may be used in the development of new approaches to the therapy of intracranial hypertension of various etiologies and methods of CNS detoxification.